Toward understanding the prevalence and purpose of placemaking among community development institutions in the United States. Issue 4 (7th August 2020) - Salzman, Ryan; Lopez, Jarett
ABSTRACT: Placemaking is a form of public engagement that impacts community development by building social capital, motivating public policy, and shaping real estate development. Popular across public-focused industries, placemaking permeates strategies for community development. This project seeks to elucidate the extent to which community development-centered institutions engage in placemaking and for what reasons. The institutions of focus in this study are community development corporations (CDCs). Employing a survey of CDC associates, the data reveal that placemaking is, in fact, a well-known and oft-practiced strategy among CDCs for myriad reasons – among them an alignment and reliance on local assets – all with the ultimate end of developing communities across the United States.